Artistic knowledge and practices of hybrid art based on the analysis of Malaysian artists’ artworks - Anak Michael, Valerie; Abd Rahman, Khairul Aidil Azlin; Abdul Shukor, Shureen Faris; Mohd Ali, Noor Azizi (e-International Publishing House, 2020)
The objective of this paper is to identify the artistic knowledge and practices of hybrid art among Malaysian artist’s artworks. The purpose is to analyze the artistic knowledge through Malaysian artist’s artworks. Ten selected artworks from the multidisciplinary artists had been choose. The researchers applied observation method to select the artworks that have the element of hybrid art and Kawakita Jiro method for the purpose of clustering the attributes for the artistic knowledge and practices of hybrid art. The finding shows that the advancement of technology, and freedom in exploring the material have affected the creation of hybrid artworks production.